An Early Case of Fat Embolism Syndrome Occurring Following Polytrauma. Issue 1 (January 2021) - Millen, Janelle-Cheri A.; Watson, Carrie; Cain, John M.; Hagan, Joshua; Richards, Winston T.; Taylor, Dana; Ang, Darwin; Clark, Jason M.
Fat embolism syndrome (FES) is a clinical entity occurring due to the presence of fat particles in the microcirculation, typically manifesting 12-72 hours after long bone trauma with respiratory distress, altered mental status, and petechial rash. Our case is that of a 17-year-old girl who suffered multiple orthopedic injuries without intracranial trauma after being a pedestrian struck by a vehicle. Despite presenting with a normal Glasgow Coma Score (GCS), within 4 hours of presentation, she was noted to have an acute mental status change to a GCS 7 with a normal computed tomography brain. Magnetic resonance imaging of the brain was suggestive of FES which, in this patient, had a rapidly progressing course with the development of severe cerebral edema and intracranial hypertension refractory to maximal medical therapy. Our patient required bilateral craniectomies for intracranial decompression and progressed over a 2-month hospital course to have subsequent cranioplasty and functional neurologic improvement. FES requires a high index of clinical suspicion in the presence of long bone fracture with unexplained altered mental status. The clinical course can be rapidly progressing with the development of intracranial hypertension which may benefit from surgical decompression with optimistic prognosis.